Nickel oxide nanoparticles as a saturable absorber for an all-fiber passively Q-switched erbium-doped fiber laser - Nady, A.; Ahmed, Mahmoud Hazzaa M.; Latiff, Anas Abdul; Numan, Arshid; Raymond Ooi, C.H.; Harun, Sulaiman Wadi (IOP Publishing, 2017)
Nickel oxide (NiO) nanoparticles were synthesized by a facile sonochemical method to fabricate saturable absorber (SA) composite film with a modulation depth of 39% and saturation intensity of 0.025 MW cm-2. By inserting the NiO SA into a laser cavity, a stable Q-switched operation is achieved at 1561.2 nm. The laser has a pump threshold of 25 mW, a pulse repetition rate tunable from 19.57 to 52.18 kHz, a high signal-to-noise ratio of 55 dB and a minimum pulse duration of 5.2 μs. Such results imply that NiO nanoparticles are a comparable candidate for an SA in passively Q-switched fiber lasers at a low pump intensity. To the best of our knowledge, this is the first demonstration of a fiber laser based on NiO SA.